MEDIA INFORMASI VIRTUAL REALITY UNTUK MEMPROMOSIKAN SEKOLAH DI MASA PANDEMI (Elkom: Jurnal Elektronika dan Komputer, 2023)
School promotions were carried out directly by visiting junior highschools, during a pandemic this can’t be done. In an effort to attractprospective new students at SMK PGRI 2 Salatiga, it is necessary toinnovate by adding promotional media that can be accessed by the widercommunity. Information distribution can be done through social mediaand the school's YouTube channel. Information media was chosen asvirtual reality in the form of 360° videos to display school facilities andprivileges.The measurement indicators used in this study are behavior, interactivity,and sound to find out whether the virtual environment can affect theinterest of prospective students at SMK PGRI 2 Salatiga. In addition, theinteractivity of the video when it is played and the sound of theenvironment in the video can give immersive in a school environment.The results of this study by the majority of respondents stated thatpromotional media virtual reality in the form of 360° videos is appropriatefor use for school promotions during a pandemic, as an effort to increasethe number of new students.